If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-23) + s = 0 -23 + s = 0 Solving -23 + s = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + s = 0 + 23 Combine like terms: -23 + 23 = 0 0 + s = 0 + 23 s = 0 + 23 Combine like terms: 0 + 23 = 23 s = 23 Simplifying s = 23
| y-(-6)=(.875)(x-6) | | c^2-15c+56=0 | | -x^2+x+18=0 | | -2y+1y-5=11+5 | | 3x^2+47=-30 | | c^2-3c+9=0 | | 6+2s=7 | | 4x-14=-6 | | 9x=-63 | | 3y+1-3y= | | -x=-46 | | x^3-32=0 | | x^4-(2.9)x^2+(8.5)=0 | | 5x+2y=-10 | | -4=3-y | | 4x^2-126=5x^2+25x | | 3r^2-5r-12=0 | | 400=16t(10-t) | | 5=4y-7 | | a^2-5.5a+7.5=0 | | 4x-2(3x-7)=3-5(x-4) | | Y=10x | | 40=8t(7-2t) | | 5a^2-22a+8=0 | | 11=3y-4 | | 16x^2+8x+4=0 | | -98=4.9t(8-t) | | -15x=-4x^2+25 | | 2x^2-8x-14=0 | | 4x^2+12x+9-(9x^2+42x+49)=0 | | -6f+13=2f+11 | | 0.9n=18.0 |